1983
DOI: 10.1192/bjp.142.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Behavioural Assessment by Computer

Abstract: An automated assessment interview was given by a microcomputer to 26 randomly selected patients, referred for treatment of phobias. The results were compared with those of conventional clinical assessment by experienced behaviour therapists. Ratings of overall severity and intensity of specific types of agoraphobia and social phobia were derived from the computer interview, and correlated very closely with global ratings by the clinician and also with an independent structured clinical assessment. The computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In studies comparing paper-and-pencil and computeradministered attitude and personality questionnaires, the findings have been equivocal. Studies comparing these two administration modes have found that respondents completing questionnaires on a computer admitted more anxiety symptoms and scored lower on a lie scale (Evan & Miller, 1969), reported more fear (Carr & Ghosh, 1983), gave fewer socially desirable responses (Kiesler & Sproull, 1986;Martin & Nagao, 1989), and were less likely to over-report their SAT scores (Martin & Nagao, 1989). However, other studies (Erdman, Klein, & Griest, 1983;Kantor, 1991;Katz & Dalby, 1981;Lukin, Dowd, Plake, & Kraft, 1985;Millstein, 1987;Rozensky, Honor, Rasinski, Tovian & Herz, 1986;Skinner& Allen, 1983;White, Clements, & Fowler, 1985;Wilson.…”
Section: Mmentioning
confidence: 99%
“…In studies comparing paper-and-pencil and computeradministered attitude and personality questionnaires, the findings have been equivocal. Studies comparing these two administration modes have found that respondents completing questionnaires on a computer admitted more anxiety symptoms and scored lower on a lie scale (Evan & Miller, 1969), reported more fear (Carr & Ghosh, 1983), gave fewer socially desirable responses (Kiesler & Sproull, 1986;Martin & Nagao, 1989), and were less likely to over-report their SAT scores (Martin & Nagao, 1989). However, other studies (Erdman, Klein, & Griest, 1983;Kantor, 1991;Katz & Dalby, 1981;Lukin, Dowd, Plake, & Kraft, 1985;Millstein, 1987;Rozensky, Honor, Rasinski, Tovian & Herz, 1986;Skinner& Allen, 1983;White, Clements, & Fowler, 1985;Wilson.…”
Section: Mmentioning
confidence: 99%
“…Computerized questionnaires have been shown to be reliable and valid in the assessment of a number of psychological disorders, including: alcohol related illness (Lucas et al 1977), depression (Carr et al 1981) and phobias (Carr & Ghosh, 1983). To the patients, they are as acceptable as paper and pencil tests (Palmer & Keyser, 1984;Moore et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…All the reported studies so far on computer-based clinical procedures have agreed that the results that emerged from such interactions were as accurate and valid as those obtained by human clinicians. Further, Carr and Ghosh (1983b), in a study on phobia patients, concluded that some of their clients found the computer-based interview more acceptable and found it easier to communicate with the computer than with the clinician.…”
Section: Human-computer Interactionmentioning
confidence: 99%
“…Nevertheless, there seems to be a broadly held conviction that behavioral and emotional malfunctioning constitutes a problem of a considerable prevalence (e.g., Sines, 1980). Existing therapeutic procedures often require the expertise and the actual involvement of specialist therapists and lengthy durations of management (Carr and Ghosh, 1983b;Carr, Ghosh and Ancill, 1983). This situation effectively has meant the restriction of such expertise to specialist behavioral units, out of reach of many sufferers (Carr and Ghosh, 1983b), as well as long client waiting lists.…”
Section: Human-computer Interactionmentioning
confidence: 99%
See 1 more Smart Citation